Pelatihan Optimalisasi Digital Marketing Menggunakan TikTok Pada UMKM Desa Rawa Panjang - Frisma Handayanna; Maryanah Safitri; Tri Santoso (CV. Multi Kreasi Media, 2025)
Optimizing digital marketing through the TikTok platform for MSMEs in Rawa Panjang Village. MSMEs in this village face challenges in utilizing digital technology to promote their products. With the growing use of social media, TikTok has become an effective platform for marketing products to a wider audience, especially the younger generation. This training is carried out using training methods that include creating creative content, appropriate marketing techniques, and maximizing TikTok features. MSMEs make a significant contribution to the regional economy by creating jobs and strengthening the purchasing power of local communities. Through this training, MSMEs in Rawa Panjang Village can increase the visibility of their products, attract more customers, and increase sales turnover. The results of this training have a positive impact on local economic development by empowering MSMEs to be more adaptive to digital marketing trends.